2023
DOI: 10.3389/fmicb.2023.1092729
|View full text |Cite
|
Sign up to set email alerts
|

Effects of several flavonoids on human gut microbiota and its metabolism by in vitro simulated fermentation

Abstract: IntroductionFlavonoids have antiviral, antitumor, anti-inflammatory, and other biological activities. They have high market value and are widely used in food and medicine fields. They also can regulate gut microbiota and promote human health. However, only a few flavonoids have been reported for their regulatory effects on human gut microbiota.MethodsThe effects of hesperidin, hesperetin-7-O-glucoside, hesperetin, naringin, prunin, naringenin, rutin, isoquercitrin, and quercetin on gut microbiota structural an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…This trend was previously described for both taxa in response to a flavonoid-enriched apple intervention in healthy adults [ 46 ]; for Sutterella abundance in response to lignan-rich interventions (e.g., flaxseed meal [ 47 , 48 ] and psyllium husk [ 49 ]; and for Lactobacillus abundance in response to other flavonoid-rich interventions [ 14 , 50 ]. There is previous evidence that flavonoids promote Lactobacillus growth [ 51 ], and several Lactobacillus spp., are capable of metabolizing both flavonoids and lignans [ 52 , 53 ]. It is important to note that other studies observed either no change in Lactobacillus abundance [ 54 ] or a decrease in Sutterella abundance [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This trend was previously described for both taxa in response to a flavonoid-enriched apple intervention in healthy adults [ 46 ]; for Sutterella abundance in response to lignan-rich interventions (e.g., flaxseed meal [ 47 , 48 ] and psyllium husk [ 49 ]; and for Lactobacillus abundance in response to other flavonoid-rich interventions [ 14 , 50 ]. There is previous evidence that flavonoids promote Lactobacillus growth [ 51 ], and several Lactobacillus spp., are capable of metabolizing both flavonoids and lignans [ 52 , 53 ]. It is important to note that other studies observed either no change in Lactobacillus abundance [ 54 ] or a decrease in Sutterella abundance [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Lachnoclostridium , was inversely correlated with phenolic acid consumption. While we did not identify phenolic acid-specific responses in the existing literature, inverse relationships were observed between Lachnoclostridium and other polyphenols in vitro [ 51 ] and in vivo [ 108 ].…”
Section: Discussionmentioning
confidence: 99%
“…When scrutinizing the effects of supplements concerning genera-based disparities, discernible positive impacts emerged. Prevotella is typically linked to diets abundant in plant-derived fibers, non-western carbohydrate profiles 84 , and flavonoid fermentation 85 , which might be related to the NSupple_ Silybum effect. This genus, known for its anti-obesogenic attributes through propionate production 86 , demonstrated marked benefits following the administration of NSupple_ Silybum .…”
Section: Discussionmentioning
confidence: 99%
“…Naringin and naringenin can directly regulate the intestinal microbiota and its metabolism. Naringin significantly reduces the abundance of gastrointestinal disease-related bacteria (e.g., Lachnoclostridium and Bilophila ) and enhances probiotic content in experiments [ 121 ]. Naringenin can regulate the growth and gene expression pattern of intestinal commensal microorganisms through interaction and activate genes related to cellular metabolism [ 122 ].…”
Section: Therapeutic Potential Of Naringin and Naringenin In Long Covidmentioning
confidence: 99%